Desvio urinário permanente por anastomose com segmento ileal - Silva, A. R. C.; Ramos, J. R. A.; Machado, L. F. P.; Hatschbach, E.; Castro, V. M.; Nunes, H. A. (Brazilian Journal of Veterinary Research and Animal Science, 2004)
O artigo não apresenta resumo.